Awareness of ASHA workers of low endemic area regarding malaria: a qualitative analysis - Pathak, Nidhi; Baliga, Sulakshana S.; Walvekar, Padmaja R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Under the community-based approach, Accredited Social Health Activist (ASHA) is designated to address early detection, management and prevention of malaria at the community level. Majority of ASHAs in high risk areas are aptly trained for these tasks but ASHAs in many low endemic areas are insufficiently trained and hence may lack awareness about malaria and its prevention and surveillance. New operational guidelines for malaria elimination by Govt. of India has tasked ASHAs of category 1 areas like Belagavi for passive case detection and contact tracing apart from spreading health awareness about its prevention. Good knowledge and practices regarding malaria among ASHA workers is thus pertinent for efficient case detection and surveillance at grass root levels. The objective of the study was to assess the awareness of ASHA workers regarding malaria. Methods: A qualitative study was conducted from January to June 2017 using eight focus group discussions among 50 ASHA workers of rural area of Belagavi selected by purposive sampling. The responses were open ended and were recorded in same sequential manner after being translated to English from local language. Each interview transcript was read several times, and meaning units were extracted independently. Results: Findings revealed that majority of them had poor knowledge regarding collection of blood smears and none of them were aware about anti-malarials. Only half of ASHA workers were aware of vector control activities, very few were aware about anti-larval activities while less than half were aware about source reduction activities. Conclusions: The discussions highlighted a need for refresher training for effective capacity building of grassroot health workers especially in low endemic area.